A new species of Oligodon Fitzinger, 1826 from the Langbian Plateau, southern Vietnam, with additional information on Oligodon annamensis Leviton, 1953 (Squamata: Colubridae) - Nguyen, Hung Ngoc; Tran, Bang Van; Nguyen, Linh Hoang; Neang, Thy; Yushchenko, Platon V.; Poyarkov, Nikolay A. (PeerJ, 2020)
We describe a new species of Oligodon from the highlands of the Langbian Plateau, southern Truong Son Mountains, Vietnam, based on morphological and molecular phylogenetic analyses. The new species, Oligodon rostralis sp. nov is distinguished from its congeners by the following morphological characters: medium size in adults (male TL = 582 mm); small and broad head with long protruding snout; dorsal scale row formula 15-15-13; 167 ventrals, 47 subcaudals; single preocular, single postocular; loreal and presubocular absent; six supralabials, third and fourth entering orbit; six infralabials, anterior four contacting first pair of chin shields; internasals separate from prefrontals; nasal divided; single anterior and two posterior temporals; cloacal plate undivided; hemipenes short, bilobed, bifurcating in anterior one third of their length, extending to 8th subcaudal, lacking spines and papillae, with a prominent transverse flounces and distal calyces; six maxillary teeth, the posterior three enlarged; dorsal pattern consisting of 14+4 large dark-brown blotches and a bright-orange vertebral stripe on tail and dorsum; and ventral surfaces in life cream laterally with dark quadrangular spots; dark temporal streak present, edged with white. We also provide additional information on O. annamensis, including a morphological dataset of all specimens known from natural history collections and confirmation of an earlier record of O. annamensis from Cambodia. We also provide the first record of O. annamensis for Dak Lak Province. Phylogenetic analyses of mtDNA genes (3,131 bp of 12S rRNA, 16S rRNA and cyt b) suggest sister relationships of Oligodon rostralis sp. nov. and O. annamensis and place them in one clade with the O. cyclurus and O. taeniatus species groups, which is concordant with previous studies on the phylogenetic relationships of Oligodon. Our study demonstrates high level of herpetofaunal diversity and endemism of Langbian Plateau and further supports the importance of this area for conservation herpetofaunal diversity in Indochina.
Keywords: Oligodon rostralissp. nov.; Cambodia; Truong son mountains; Annamites; Endemism; Hemipenis morphology; Taxonomy; Distribution; Morphology; Mtdna